Nonlinear relationship between exchange rate volatility and economic growth - Andrew Phiri (Economics and Econometrics Research Institute (EERI), 2018)
In this paper, we challenge the traditional assumption of a linear relationship between exchange rate volatility and economic growth in South Africa. By using data collected from 1970 to 2016 applied to a smooth transition regression (STR) model, we are able to prove that the exchange rate-economic growth correlation is indeed nonlinear within the sampled time period. In particular, we find that regime switching behaviour is facilitated by government size in which exchange rate volatility positively and significantly influences economic growth when growth in government spending is below 6 percent. Above this 6 percent threshold, volatility exerts an insignificant effect on economic growth. In light of the adoption of a free floating exchange rate regime by the Reserve Bank, our results emphasize the importance of the role which fiscal authorities play on the extent to which exchange rate movements affect economic growth.
Keywords: C01; C22; C52; E52; F31; O40; 330; Exchange rates; economic growth; smooth transition regression (STR) model; thresholds; nonlinearity; volatility; South Africa; monetary policy; fiscal policy